Self-Managed Leisure, Satisfaction, and Benefits Perceived by Disabled Youth in Northern Spain - Doistua, Joseba; Lazcano, Idurre; Madariaga, Aurora (Frontiers in Psychology, 2020)
Positive leisure is widely accepted as contributing to the development of self-autonomy and well-being of young people during their transition to adulthood (Coleman, 2011; Glendenning et al., 2003). However, there has been little research on these issues among young people with disabilities. In this study, we analyzed the relationship between self-managed leisure, satisfaction with leisure, and emotional, cognitive, and behavioral benefits as perceived by young people with disabilities. The sample consisted of 400 young people (48.8% female) with disabilities (hearing, physical, intellectual, and visual), aged between 15 and 29 years, who live in the Basque region of northern Spain. Results revealed the following conclusions. First, gender and type of disability relate to the degree of self-management associated with leisure. Second, there was a significant association between the degree of satisfaction with leisure and level of self-management associated with leisure and this relationship varied by disability type but not gender. Third, leisure independently organized by young people (self-managed) was associated with higher perceived psychological benefits (emotional and cognitive) connected with their leisure engagement.